THE DEMAND OF DEMOCRATIC LEADER IN SOUTHEAST ASIA: A CASE OF THAI SOCIETY - Bhothisawang, Paithoon (PEOPLE: International Journal of Social Sciences, 2017)
Thailand is located in Southeast Asia. Thailand's democracy was still struggling that is a military coup by the loop 13 times. Every time a new constitution to allow more democratic, the last time was on May 22, 2014. But many Thai people have come to congratulate and welcome to new leader from powerful military. The research objectives are to analysis the leader types that Thai society wants and the factors that influence the demand. Then create a mathematical equation. To predict which type of leader depends on what factor. This methodology has been sampled from the voters, total 400 samples to analysis with “stepwise multiple regression analysis”. The finding showed demand of Thai society that the democratic leader with an average of 71.45out of 100 points. Factors that affect democratic leader needs caused by 4 factors that are the policy of the political party, that are the favorite of most people.Secondly, to promote the industrial development to make people earn and have work. Next is ability to organize society And the last are the right and the freedom to express in political, right to elect the leader. The equation can be:Want Democratic Leader = 45.76 +.28 policy of govt.party +.26 industrial.estate. -.24 social.order.ability + .07 Right.freedom. The research outcome can suggest: Should invent the "new" policies should be “be to one’s taste” of people, should be on promoting industrial development, should promote freedom of opportunity and should increase the ability to organize social order. Research methods should be expanded to bring that research into a new political theory in the future.